Proceedings of the 3rd International Workshop on Green and Sustainable Software 2014
DOI: 10.1145/2593743.2593749
|View full text |Cite
|
Sign up to set email alerts
|

Green mining: energy consumption of advertisement blocking methods

Abstract: Extending battery life on mobile devices has become an important topic recently due to the increasing frequency of smartphone adoption. A primary component of smart phone energy consumption is the apps that run on these devices. Many apps have embedded advertising and web browser apps will show ads that are embedded on webpages. Other researchers have found that advertising libraries and advertisements tend to increase power usage. But is the converse true? If we use advertisement blocking software will we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Mobile ads are personalized through attributes, trends [38], and behaviour [39], etc. Rasmussen and colleagues [40] analyzed the effects of advertisement blocking methods on energy consumption. Book and colleagues [41] observe a steady increase in the number of permissions that Android ad libraries are able to use, after examining a sample of 114,000 apps.…”
Section: Related Workmentioning
confidence: 99%
“…Mobile ads are personalized through attributes, trends [38], and behaviour [39], etc. Rasmussen and colleagues [40] analyzed the effects of advertisement blocking methods on energy consumption. Book and colleagues [41] observe a steady increase in the number of permissions that Android ad libraries are able to use, after examining a sample of 114,000 apps.…”
Section: Related Workmentioning
confidence: 99%
“…In a separate study, Rasmussen et al [48] found that a system with Ad-blocker, in most cases, is more energy efficient than systems without Ad-blockers.…”
Section: Improving Energy Efficiencymentioning
confidence: 99%
“…To capture energy consumption profiles of the web server for HTTP/2 and HTTP/1.1, we have used Green Miner [34] [34], [49].…”
Section: Green Minermentioning
confidence: 99%